(untitled) (Journal of Bangladesh College of Physicians and Surgeons, 2024)
Artificial intelligence (AI) is an essential tool in the medical sector that contributes significantly to medical imaging, medical pathology, histology, genomic study, predictive analysis, etc. It is being increasingly used not only in breast and lung cancer diagnosis and screening, and genetic disease identification but also in personalized decision-making during the treatment of these diseases. The quality and availability of unbiased data is a key challenge. Algorithmic bias and interpretability are significant concerns as well. Improving the use of AI in medical diagnostics could be achieved through continuous monitoring, access to highly accurate datasets, and timely intervention by healthcare professionals. J Bangladesh Coll Phys Surg 2024; 42: 379-382